Vocalization and sociality of Mashona mole-rat (Fukomys darlingi) - Dvořáková, Veronika (Jihočeská univerzita, 2010)
Vocal repertoire of adult Mashona mole-rat (Fukomys darlingi) was described and compared to other subterranean rodents in dependence on social system. Twelve call types have been identified, among them one mechanical sound. Mashona mole-rats vocalize in low frequencies (3,55 kHz) as is usual in subterranean rodents. Mashona mole-rat possess three contact, three aggressive, three distress and two mating calls. This structure of vocal repertoire corresponds to the structure of the vocal repertoire of the Ansell's mole-rat.Preliminary screening for the individually distinct call type has been performed
Vocalization and sociality of Mashona mole-rat (Fukomys darlingi)